Analysis of hospital‐based emergency department visits for dental caries in the United States in 2008. (3rd December 2013) - Walker, Andre; Probst, Janice C.; Martin, Amy B.; Bellinger, Jessica D.; Merchant, Anwar
Abstract Objectives Using nationally representative data, we examined differences in dental care utilization in emergency departments (EDs) among working age adults associated with rural residence and lack of health insurance. Methods We used data from the 2008 Nationwide Emergency Department Sample, restricted to working age adults (ages 19‐64; 16, 928, 424 observations). The dependent variable was a principal diagnosis of dental caries. The primary independent variable was patient's area of residence, rural versus urban. The control variables were payer, age, gender, median income, region, and admission timing. Logistic regression analysis was performed to determine the association with residence, payer, and other covariates. Multivariate logistic regression models were estimated. Results In 2008, there were an estimated 74 million ED visits among working adults ages 19‐64 in the United States. Dental caries accounted for between 0.2 percent and 1.0 percent of all visits, depending on patient characteristics. Rural patients were significantly more likely than urban patients to have dental visits. Dental visits were more prevalent among patient with government insurance or self ‐pay relative to the privately insured. Conclusions The Affordable Care Act may reduce the proportion of self‐pay visits for dental care. Medicaid expansion may not result in improved dental use among Medicaid patients unless dental services are covered and dental practitioners appropriately engaged.